Schizophyllum commune Lipase Production on Pretreated Sugarcane Bagasse and Its Effectiveness - Yew Chee Kam; Siew Ling Hii; Cheryl Yan-Yi Sim; Lisa Gaik Ai Ong (International Journal of Polymer Science)
Schizophyllum commune UTARA1 was used for lipase production under solid state fermentation (SSF) of sugarcane bagasse (SB) impregnated with used cooking oil medium. Pretreatments of steam, microwave, hydrochloric acid (HCl), sodium hydroxide (NaOH), and their combinations, such as steam-assisted HCl, steam-assisted NaOH, microwave-assisted HCl, and microwave-assisted NaOH, on the milled SB, were done prior to SSF to investigate their effects on lipase production via SSF. The highest lipase activity among the pretreated SB was 0.200 U/gSB, using steam-assisted HCl treated SB, which is lower than the lipase activity produced from the untreated SB, which was 0.413 U/gSB. Scanning Electron Microscope (SEM) imaging showed significant rupture of the SB structure after steam-assisted-HCl pretreatments where the thin walls of the SB pith were wrinkled and collapsed, with no distinctive cell wall structure. The HCl pretreated SB gave the highest crystallinity index (CrI), 91.43%, compared to the untreated, 61.90%. Conversely, microwave and NaOH pretreatments reduced the CrI, which were 46.15% and 43.36%, respectively. In this study, the results obtained indicated that pretreated SB did not improve the lipase production of Schizophyllum commune UTARA1 under SSF.